2022
DOI: 10.1186/s13756-022-01070-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of respirator versus surgical masks on SARS-CoV-2 acquisition in healthcare workers: a prospective multicentre cohort

Abstract: Background There is insufficient evidence regarding the role of respirators in the prevention of SARS-CoV-2 infection. We analysed the impact of filtering facepiece class 2 (FFP2) versus surgical masks on the risk of SARS-CoV-2 acquisition among Swiss healthcare workers (HCW). Methods Our prospective multicentre cohort enrolled HCW from June to August 2020. Participants were asked about COVID-19 risk exposures/behaviours, including preferentially w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Similar to the findings of Belan et al 7 , a prospective cohort study at nine healthcare institutions from Switzerland found household exposure to be the strongest risk factor (adjusted hazard ratio 10.1; 95% CI 7·5−13·5) for both HCW SARS-CoV-2 swab positivity and seroconversion in a multivariate regression analysis. 11 This study also found no significant difference between the use of a filtering facepiece class 2 (FFP2) respirator versus the use of a surgical mask 11 which is consistent with the updated systematic review of observational studies for risk factors for COVID-19 among HCWs mentioned above, albeit recognizing the limitations of observational studies. 4 Other high quality systematic reviews have not found any differences for increased risk of transmission to HCWs for other respiratory viruses when comparing medical/surgical masks versus N95 respirators.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Similar to the findings of Belan et al 7 , a prospective cohort study at nine healthcare institutions from Switzerland found household exposure to be the strongest risk factor (adjusted hazard ratio 10.1; 95% CI 7·5−13·5) for both HCW SARS-CoV-2 swab positivity and seroconversion in a multivariate regression analysis. 11 This study also found no significant difference between the use of a filtering facepiece class 2 (FFP2) respirator versus the use of a surgical mask 11 which is consistent with the updated systematic review of observational studies for risk factors for COVID-19 among HCWs mentioned above, albeit recognizing the limitations of observational studies. 4 Other high quality systematic reviews have not found any differences for increased risk of transmission to HCWs for other respiratory viruses when comparing medical/surgical masks versus N95 respirators.…”
supporting
confidence: 83%
“…The identified risks to nurses and nurse’s aides may be related to the amount of close contact, hands-on care provided and is consistent with a recent prospective cohort study which assessed the risk by HCW category. 11 An unexplained finding is the decreased risk of COVID-19 among HCWs in LTCFs with regular COVID-19 patient-facing activities. One might expect an increased risk in this setting but it is possible that the HCWs in the LTCFs were previously immunized or infected during the initial wave of COVID-19.…”
mentioning
confidence: 99%
“…Despite the contradictory data during the pandemic [70] , there are several clinical and theoretical arguments in favor of N95 respirators in contact with infected patients. Studies during the pandemic suggested the superiority in terms of filtration of N95 respirators compared to surgical masks, and in some cases [71] , a lower risk of contamination of health care workers. It is now clear that the presence of fine particles exhaled by infected patients and the risk situations in hospitals [3] are two factors that argue in favor of N95 respirators.…”
Section: Discussion-conclusionmentioning
confidence: 99%
“…It is difficult to rely on the randomised clinical trial to evaluate the real-world effectiveness of FFP vs. surgical masks for protecting HCW from infection, as it is impossible to control all confounding factors. Some evidence indicates potential benefits for HCW and patients with use of FFP’s 11 , 12 , but successful infection control will include a bundle of measures, not just RPE. Current guidance on use of respiratory protection for healthcare workers suggests use of FFP3 respirators for working with patients with known or suspected infectious diseases transmitted ‘wholly by the airborne route’ or when carrying out AGPs on patients with an infectious disease spread at least partially by droplet or airborne routes, or as a precautionary measure if the hazard is unknown.…”
Section: Discussionmentioning
confidence: 99%